Measuring family functioning in families with parental cancer: Reliability and validity of the German adaptation of the Family Assessment Device (FAD) - Beierlein, Volker; Resch, Franz; Herzog, Wolfgang (Journal of psychosomatic research, 2017)
Objective The concept of family functioning is gaining importance in psycho-oncology research and health care services. The Family Assessment Device (FAD) is a well-established measure of family functioning. Psychometric properties inherent in the German 51-item adaptation of the FAD are examined in different samples of families with parental cancer. Methods Acceptance, reliability, and validity of FAD scales are analysed in samples from different study settings (N=1701 cancer patients, N=261 partners, N=158 dependent adolescent children 11 to 18years old). Results Missing items in the FAD scales (acceptance) are rare for adults (<1.1%) and adolescent children (<4.4%). In samples of adults and older adolescents (15 to 18years), all FAD scales except for the Roles scale are significantly reliable (0.75≤Cronbach's α≤0.88). The scales correlate highly (0.46≤Pearson's r≤0.59) with the criterion satisfaction with family life (convergent validity), and have smaller correlations (0.16≤r≤0.49) with measures of emotional distress and subjective well-being (divergent validity). In most FAD scales, adults seeking family counselling report worse family functioning (0.24≤Cohen's d≤0.59) than adults in other samples with parental cancer (discriminative validity). Conclusion Overall, the German 51-item adaptation of the FAD reveals good acceptance, reliability, and validity for cancer patients and their relatives. Particularly the scale General Functioning shows excellent psychometric properties. The FAD is suitable in the assessment of families with parental cancer for adults and adolescents older than 11years.
Received 31 October 2016, Accepted 18 November 2016, Available online 21 November 2016
Gesehen am 10.10.2018